Taxation challenges in a digital economy the case of the People Republic of China. - Terada-Hagiwara, Akiko (Potential exports and nontariff barriers to trade.)
The digital economy is growing rapidly across the globe and, among developing countries, the PRC is a leader. Despite its promise, the global digital economy also poses many challenges, including tax base erosion and profit shifting. The brief looks at initial efforts by the PRC to address these challenges and proposes the next steps. It recommends that the country continues to participate in the international taxation forum, adopt unilateral measures, improve its tax registration system, and strengthen its tax administration capacity.